Pengaruh Pemberian Hindmilk Terhadap Peningkatan Berat Badan (BB) Bayi Berat Lahir Rendah (BBLR) di Rumah Sakit Umum Daerah Kabupaten Malinau - Denny Kristiani Denny Kristiani; Aries Abiyoga; Desy Ayu Wardhani; Sumiati Sinaga (JURNAL KESEHATAN KARTIKA, 2026)
Background: Low birth weight (LBW) is a global health issue with a prevalence that remains high; approximately 20 million babies per year fall into the LBW category, including in Indonesia. LBW infants are at risk of serious complications and long-term growth and developmental disorders. Objective: This study aims to analyze the effect of hindmilk administration on weight gain in LBW infants at the Malinau District General Hospital. Methods: This study used a quasi-experimental design with a pretest-posttest one-group design. The sample consisted of 14 LBW infants in the Perinatology Ward of Malinau District General Hospital, selected using purposive sampling. Results: The average birth weight of the low birth weight infants before receiving hindmilk was 2082.14 grams. After the hindmilk intervention, the average infant weight increased to 2143.57 grams with a standard deviation of 364.64 grams; the range of infant weights increased from 1440 grams to 2590 grams. The results of the Paired Sample T-Test showed a p-value of 0.001 (p < 0.05), indicating a statistically significant difference between body weight before and after the intervention. Conclusion: There is a significant effect of Hindmilk administration on weight gain in low birth weight infants at Malinau Regional General Hospital. Therefore, Hindmilk administration can be recommended as an effective nutritional intervention in the management of low birth weight infants, particularly in areas with limited resources.